Security and trust issues in internet of things : blockchain to the rescue - Sharma, Sudhir Kumar; Bhushan, Bharat, 1949-; Unhelkar, Bhuvan (Boca Raton : CRC Press, 2020)
The purpose of this edited book is to present and showcase the basic fundamentals, applications, and integration of both IoT and Blockchain. The trend of applying Blockchain to IoT is rapidly growing because it helps to overcome various challenges faced by IoT, from smart manufacturing to unmanned aerial vehicles. Thise book aims to showcase the basics of both IoT and Blockchain as well as the integration and challenges for existing practitioners. Thise book initiates conversations among technologists, engineers, scientists, and clinicians to synergize their efforts in producing low-cost, high-performance, highly efficient, deployable IoT systems. Thise book is theory-based and is useful for engineers from various disciplines, including industrial engineering, computer science, electronics, telecommunications, electrical, agricultural, and cybersecurity, along with researchers, professionals, and students.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; Blockchains (Databases); COMPUTERS / Computer Science